2004
DOI: 10.1159/000080791
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Various Chemical Disinfectants versus Cleaning Combined with Heat Disinfection on <i>Pseudomonas</i> Biofilm in Hemodialysis Machines

Abstract: The development of bacterial biofilms in the hydraulic circuit of hemodialysis machines is routinely prevented by frequent use of a variety of chemical and heat disinfection strategies. This study compared the effectiveness of several chemical disinfectants, commonly used either alone or in combination with a treatment regimen that involved cleaning plus heat disinfection using an in vitro Pseudomonas biofilm model. Effectiveness of these procedures was evaluated using total and viable biomass quantitation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 10 publications
1
11
0
Order By: Relevance
“…Only the addition of ultrasonic exposure during disinfectant exposure increased the disinfectant effects to nearly full efficacy. These results underline similar findings in previous studies on the effects of ultrasound exposure as well as other mechanical treatments or heat exposure (Madge and Jensen 2002;Holmes et al 2004;Dong et al 2013).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Only the addition of ultrasonic exposure during disinfectant exposure increased the disinfectant effects to nearly full efficacy. These results underline similar findings in previous studies on the effects of ultrasound exposure as well as other mechanical treatments or heat exposure (Madge and Jensen 2002;Holmes et al 2004;Dong et al 2013).…”
Section: Discussionsupporting
confidence: 91%
“…These results underline similar findings in previous studies on the effects of ultrasound exposure as well as other mechanical treatments or heat exposure (Madge and Jensen ; Holmes et al . ; Dong et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…Heat treatment is an established technique that has been used to decontaminate medical devices, ensure aseptic inoculation, and aid in therapeutic preparations (17,18). However, for M. tuberculosis, reports have shown that short slide flaming or drying on a hot block is insufficient to completely inactivate all bacilli (19,20).…”
mentioning
confidence: 99%
“…Another model simulated Pseudomonas aeruginosa biofilm formation in the silicone tubing used in hydraulics modules of haemodialysis machines [36 ]. Chemical removal of the biofilm using 3.3% citric acid followed by autoclaving was much more successful than other chemical treatments (sodium hypochlorite, hydrogen peroxide and peracetic acid, alone and in combination).…”
Section: Biofilmsmentioning
confidence: 99%
“…Some attempt to simulate use conditions and use relevant substrata [35,36 ], whereas some might be termed 'convenience models' [37 -39 ], which employ easily available, simple substrata such as glass or plastic. No standard methods exist for different applications.…”
Section: Biofilmsmentioning
confidence: 99%